The Complex Nature of Bilinguals' Language Usage Modulates Task-Switching Outcomes - Yang, Hwajin; Hartanto, Andree; Yang, Sujin (Frontiers in Psychology, 2016)
In view of inconsistent findings regarding bilingual advantages in executive functions (EF), we reviewed the literature to determine whether bilinguals’ different language usage causes measureable changes in the shifting aspects of EF. By drawing on the theoretical framework of the adaptive control hypothesis—which postulates a critical link between bilinguals’ varying demands on language control and adaptive cognitive control (Green & Abutalebi, 2013), we examined three factors that characterize bilinguals’ language-switching experience: (a) the interactional context of conversational exchanges, (b) frequency of language switching, and (c) typology of code-switching. We also examined whether methodological variations in previous task-switching studies modulate task-specific demands on control processing and lead to inconsistencies in the literature. Our review demonstrates that not only methodological rigor but also a more finely grained, theory-based approach will be required to understand the cognitive consequences of bilinguals’ varied linguistic practices in shifting EF.